2015
DOI: 10.1155/2015/407320
|View full text |Cite
|
Sign up to set email alerts
|

Increase in Short-Interval Intracortical Facilitation of the Motor Cortex after Low-Frequency Repetitive Magnetic Stimulation of the Unaffected Hemisphere in the Subacute Phase after Stroke

Abstract: Low-frequency repetitive transcranial magnetic stimulation of the unaffected hemisphere (UH-LF-rTMS) in patients with stroke can decrease interhemispheric inhibition from the unaffected to the affected hemisphere and improve hand dexterity and strength of the paretic hand. The objective of this proof-of-principle study was to explore, for the first time, effects of UH-LF-rTMS as add-on therapy to motor rehabilitation on short-term intracortical inhibition (SICI) and intracortical facilitation (ICF) of the moto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Again, possible resolution in the early recovery stage may explain the rapid changes in CSE in the acute stage [29]. Although, the apparent CSE recovery seen in figure 1 appears strong, some previous studies have concluded that the rMT is influenced by multiple structural and functional characteristics of both cortical and spinal neurons negatively affecting its ability to act as a reliable biomarker regarding inter-hemispheric differences in excitability [7,19].…”
Section: Discussionmentioning
confidence: 93%
“…Again, possible resolution in the early recovery stage may explain the rapid changes in CSE in the acute stage [29]. Although, the apparent CSE recovery seen in figure 1 appears strong, some previous studies have concluded that the rMT is influenced by multiple structural and functional characteristics of both cortical and spinal neurons negatively affecting its ability to act as a reliable biomarker regarding inter-hemispheric differences in excitability [7,19].…”
Section: Discussionmentioning
confidence: 93%
“…In other words, unbalanced excitement of the cerebrum on the non-lesioned hemisphere adversely affects functional improvement. Since nervous activity is suppressed by LF-rTMS, the activity of the non-lesional hemisphere can be suppressed by applying LF-rTMS to the motor cortex of the nonlesional hemisphere (42), and suppression of interhemispheric inhibition of the non-lesional hemisphere indirectly increases the activity of the lesional side (43). On the other hand, highfrequency (HF)-rTMS evokes nervous activity and stimulates the motor cortex of the lesional hemisphere to enhance activity at the lesional site directly (44).…”
Section: Discussionmentioning
confidence: 99%
“…However, the disability rate has also increased accordingly. Cognitive dysfunction often follows a stoke, and a clinical report has suggested it occurs in 50–75% of patients (4). The present study first examined how miRNA-22 expression is downregulated in ischemic stroke rats, compared with a control group.…”
Section: Discussionmentioning
confidence: 99%
“…Ischemic stroke is the second major factor leading to mortality and disability in patients. Specifically, 20–50% patients will succumb or suffer from despite receiving treatment within one month following a stroke (4). With the development of modern medical science, intensive studies on the mechanism of ischemic stroke have been performed at the cellular and molecular levels (5).…”
Section: Introductionmentioning
confidence: 99%